Novel esophageal squamous cell carcinoma bone metastatic clone isolated by scintigraphy, X ray and micro PET/CT - Zhao, Bi-Zeng (World journal of gastroenterology : WJG, 2014)
AIM:To establish a Chinese esophageal squamous cell carcinoma(ESCC)cell line with high bone metastasis potency using99mTc-methylene diphosphonate(99mTcMDP)micro-pinhole scintigraphy,X ray and micropositron emission tomography/computed tomography(PET/CT)for exploring the mechanism of occurrence and development in esophageal cancer.METHODS:The cells came from a BALB/c nu/nu immunodeficient mouse,and oncogenic tumor tissue was from a surgical specimen from a 61-year-old male patient with ESCC.The cell growth curve was mapped and analysis of chromosome karyotype was performed.Approximately 1×106oncogenic cells were injected into the left cardiac ventricle of immunodeficient mice.The bone metastatic lesions of tumor-bearing mice were detected by99mTc-MDP scintigraphy,micro-PET/CT and X-ray,and were resected from the mice under deep anesthesia.The bone metastatic cells in the lesions were used for culture and for repeated intracardiac inoculation.This in vivo/in vitro experimental metastasis study was repeated for four cycles.All of the suspicious bone sites were confirmed by pathology.Real-time polymerase chain reaction was used to compare the gene expression in the parental cells and in the bone metastatic clone.RESULTS:The surgical specimen was implanted subcutaneously in immunodeficient mice and the tumorigenesis rate was 100%.First-passage oncogenic cells were named CEK-Sq-1.The chromosome karyotype analysis of the cell line was hypotriploid.The bone metastasis rate went from 20%with the first-passage oncogenic cells via intracardiac inoculation to 90%after four cycles.The established bone metastasis clone named CEK-Sq-1BM had a high potential to metastasize in bone,including mandible,humerus,thoracic and lumbar vertebrae,scapula and femur.The bone metastasis lesions were successfully detected by micro-pinhole bone scintigraphy,micro-PET/CT,and X-ray.The sensitivity,specificity and accuracy of the micro-pinhole scintigraphy,X-ray,and micro-PET/CT imaging examinations were:89.66%/32%/80%,88.2%/100%/89.2%,and 88.75%/77.5%/87.5%,respectively.Some gene expression difference was found between parental and bone metastasis cells.CONCLUSION:This newly established Chinese ESCC cell line and animal model may provide a useful tool for the study of the pathogenesis and development of esophageal carcinoma.